Effect of Duration of Accelerated Ageing on Physiological Dormancy in Teak (Tectona grandis) Seeds: Preliminary Observations - R. ANANDALAKSHMI; B. GURUDEV SINGH; V. SIVAKUMAR; R.R. WARRIER; G. CHEVANAN (Seed Research, 2026)
Studies on the duration of accelerated ageing (AA) on physiological dormancy in teak seeds revealed that AA of teak seeds for 6 days would facilitate quicker germination and mobilization of seed proteins with release of physiological dormancy.